2018
DOI: 10.1016/j.ijplas.2018.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Thermal effects on high-frequency magnetic-field-induced martensite reorientation in ferromagnetic shape memory alloys: An experimental and theoretical investigation

Abstract: Thermal effects on high-frequency magnetic-field-induced martensite reorientation in ferromagnetic shape memory alloys: An experimental and theoretical investigation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(5 citation statements)
references
References 79 publications
0
3
0
2
Order By: Relevance
“…It shows that there is a wide range of specimen geometries and types of tests discussed in the literature for which full-field measurement systems have been used. NiMnGa [171,176,191,202,206,235,263,264] NiMnTi [139] NiCoMnTi [139,147] NiMnInCu [130] NiMnSn [138] […”
Section: Classification Of the Papers Found In The Literaturementioning
confidence: 99%
“…It shows that there is a wide range of specimen geometries and types of tests discussed in the literature for which full-field measurement systems have been used. NiMnGa [171,176,191,202,206,235,263,264] NiMnTi [139] NiCoMnTi [139,147] NiMnInCu [130] NiMnSn [138] […”
Section: Classification Of the Papers Found In The Literaturementioning
confidence: 99%
“…The superelasticity/pseudoelasticity and shape memory effect of shape memory alloys (SMAs) result from a 1 st -order solid-solid phase transformation (martensitic transformation) that can be induced by thermal, mechanical, and magnetic loadings (Kiefer and Lagoudas, 2005;Arndt et al, 2006;Karaca et al, 2006;Sehitoglu et al, 2012;Chen et al, 2014;Haldar et al, 2014;Kamarád et al, 2014;Pascan et al, 2015;Cisse et al, 2016;Heczko et al, 2016;Rogovoy and Stolbova, 2016;Yin et al, 2016;Bruno et al, 2017;Zhang et al, 2018b;Chen and He, 2020;Zhang et al, 2020). The high-temperature stable parent phase (austenite) has cubic symmetry whereas the lowtemperature stable product phase (martensite) has lower symmetry, such as tetragonal, orthorhombic, and monoclinic symmetry, depending on the chemical composition.…”
Section: Introductionmentioning
confidence: 99%
“…Techapiesancharoenkil et al (2009, 2011 experimentally demonstrated the relationship between magnetic field and output strain in dynamic Ni-Mn-Ga actuators. Recent experiments in (Zhang et al, 2018a(Zhang et al, , 2018bZhang et al, 2020) focused on long-term (> 100 s) dynamic behaviour of MSMAs, revealed a new phenomenon: the accumulated heat from the intrinsic dissipation of the cyclic martensite reorientation induced by cyclic magnetic field can significantly increase the material's temperature. Under the weak ambient heat-transfer condition, the phase transformation temperature can be reached, and the martensite-to-austenite transformation can be triggered, leading to a sudden strain drop of the material.…”
Section: Introductionmentioning
confidence: 99%